Implementasi Aplikasi Sehat Indonesiaku (ASIK) dalam Pengelolaan Data Balita di Posyandu Desa Kebonsari, Candi, Kabupaten Sidoarjo - Laura Frizia Larasati; Ahmad Yusroni (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
The Sehat Indonesiaku (ASIK) Application is a key policy instrument of Indonesia's Ministry of Health designed to improve community health data management, particularly toddler data in Integrated Service Posts (Posyandu). However, implementation at the village level continues to face operational challenges. This study analyzes the implementation of the ASIK program in managing toddler data at Posyandu in Kebonsari Village, Sidoarjo Regency, using George C. Edward III's policy implementation framework. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observation, and documentation from purposively selected informants comprising Posyandu cadres, public health center midwives, and village officials. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña (2014). Findings reveal that ASIK implementation has not been optimal due to constraints across all four Edward III variables: uneven program socialization (communication), limited digital literacy and inadequate device-network infrastructure (resources), dual manual-digital recording workloads (disposition), and over-reliance on core cadres (bureaucratic structure). Nonetheless, adaptive responses including continuous training, structured task delegation, and village government support have been established. This study highlights that the success of ASIK implementation fundamentally depends on human resource readiness, effective policy communication, and institutional support at the local level.